Structure based design of a Grp94-selective inhibitor: Exploiting a key residue in Grp94 to optimize paralog-selective binding - Que, Nanette L. S. (J Med Chem, 2018)
Grp94 and Hsp90, the ER and cytoplasmic hsp90 paralogs, share a conserved ATP-binding pocket that has been targeted for therapeutics. Paralog-selective inhibitors may lead to drugs with fewer side effects. Here, we analyzed 1 (BnIm), a benzyl imidazole resorcinylic inhibitor, for its mode of binding. The structures of 1 bound to Hsp90 and Grp94 reveal large conformational changes in Grp94, but not Hsp90 that expose Site 2, a binding pocket adjacent to the central ATP cavity that is ordinarily blocked. The Grp94:1 structure reveals a flipped pose of the resorcinylic scaffold that inserts into the exposed Site 2. We exploited this flipped binding pose to develop a Grp94-selective derivative of 1. Our structural analysis shows that the ability of the ligand to insert its benzyl imidazole substituent into Site 1, a different side pocket off the ATP binding cavity, is the key to exposing Site 2 in Grp94.